1989
DOI: 10.1016/0014-5793(89)80762-8
|View full text |Cite
|
Sign up to set email alerts
|

Subtilisin enzymes: A note on time‐resolved fluorescence and circular dichroism properties

Abstract: This note briefly corrects previous information about the time-resolved fluorescence properties of preparations of subtilisin Carlsberg and subtilisin BPN'. We confirm the observation of segmental motion of the single tryptophan in subtilisin Carlsberg by analysis of the time-resolved fluorescence anisotropy, and present circular dichroism and spectroscopic data on the two proteins. Near-UV properties clearly differentiate between the two proteins. Far-UV circular dichroism confirms that the two subtilisins ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…These results indicate that the enzyme does not degrade in the presence of SDS, DTAB, or itself over a 10 h period. We conclude that subtilisin Carlsberg does not autolyze during the time of our experiments with or without surfactant, in agreement with Bayley et al (1989) who found negligible subtilisin Carlsberg autolysis at concentrations <10 mM in neutral pH. Figure 5 shows that when the ionic surfactants are added to FBSA solution, fluorescence intensity increases until near the CMC.…”
Section: Enzyme Autolysissupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that the enzyme does not degrade in the presence of SDS, DTAB, or itself over a 10 h period. We conclude that subtilisin Carlsberg does not autolyze during the time of our experiments with or without surfactant, in agreement with Bayley et al (1989) who found negligible subtilisin Carlsberg autolysis at concentrations <10 mM in neutral pH. Figure 5 shows that when the ionic surfactants are added to FBSA solution, fluorescence intensity increases until near the CMC.…”
Section: Enzyme Autolysissupporting
confidence: 91%
“…Likewise, partial unfolding of enzymes due to surfactant generally results in loss of enzymatic activity (Cruzten and Douglas, 1999;Stoner et al, 2004). However, sodium alkyl benzene sulfonate (Nacconol 90G), and sodium lauryl sulphate (Steol CS-370) increase subtilisin Carlsberg autolysis rate in a concentrated heavyduty-liquid-detergent formulation (Stoner et al, 2004), whereas sodium dodecyl sulphate (SDS) has no effect for enzyme concentrations below 10 mM (Bayley et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the fractions calculated from CD spectra have large errors inherently. Thus we estimated just the approximate fractional changes of the constituting secondary structures with Ca 2ϩ removal, considering the secondary structure fractions of NsC by Bayley et al (1989) and the basis spectra and estimation method of secondary structures by Saxena and Wetlaufer (1971). Despite large uncertainties, we are showing experimentally for the first time the progressive structural changes of sC with Ca 2ϩ binding.…”
Section: Resultsmentioning
confidence: 97%
“…The determination of individual secondary structure fractions by analyzing CD spectra has been widely used (Venyaminov and Yang, 1996). Although the fractions of ␣-helix, ␤-sheet, turn, and random coil in NsC are reported as 0.31, 0.1, 0.22, and 0.37, respectively, from the x-ray structure (Chang et al, 1978), they are found to be 0.22, 0.47, 0, and 0.31, respectively, from the CD spectrum (Bayley et al, 1989). This indicates that the fractions calculated from CD spectra have large errors inherently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation